1999
DOI: 10.1089/thy.1999.9.775
|View full text |Cite
|
Sign up to set email alerts
|

Antithyroid Drugs Inhibit Radioiodine-Induced Increases in Thyroid Autoantibodies in Hyperthyroid Graves' Disease

Abstract: Methimazole (MMI) has been reported to affect prognosis in hyperthyroid Graves' disease patients treated with radioiodine (131I). In the present study, serum concentrations of thyroxine (T4), triiodothyronine (T3), thyroglobulin (Tg), thyrotropin-binding inhibitory immunoglobulin (TBII), thyroglobulin antibody (TgAb), and thyroid-peroxidase antibody (TPOAb) were measured serially for 1 year in patients with Graves' disease after 131I treatment either given alone (group 1, 41 patients) or followed by an antithy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 25 publications
0
6
0
2
Order By: Relevance
“…Simultaneous thyrostatic medication increases the possibility of treatment failure by more than 5 times [38]. The therapy with anti-thyroid drugs immediately after radioiodine is equally associated with reduced cure rate [21,39]. We suggest that the routine use of thionamides following radioiodine has little justification as also suggested by others [40].…”
Section: Ideal Choice Of Pre-treatment With Anti-thyroid Drugs If Anymentioning
confidence: 70%
“…Simultaneous thyrostatic medication increases the possibility of treatment failure by more than 5 times [38]. The therapy with anti-thyroid drugs immediately after radioiodine is equally associated with reduced cure rate [21,39]. We suggest that the routine use of thionamides following radioiodine has little justification as also suggested by others [40].…”
Section: Ideal Choice Of Pre-treatment With Anti-thyroid Drugs If Anymentioning
confidence: 70%
“…In 1988, Velkeniers et al (14) reported that treatment failure occurred almost five times more often if ATDs were resumed after 131 I therapy of hyperthyroidism. Subsequently, the findings of other studies (15 -17) supported the view that the use of ATDs in the period after 131 I treatment reduced the cure rate from the therapy, in some cases associated with a blunted 131 I-induced increase in the titres of thyroid autoantibodies (17). However, all those studies (14-17) suffered from the drawbacks unavoidable in retrospective designs.…”
Section: Discussionmentioning
confidence: 85%
“…Recent research showed that methimazole moderately inhibited the synthesis of immunoglobulins including TSAb (14)(15)(16)(17)(18)(19)(20). In this study, we treated GO and GD patients with methimazole and examined the effect of the drug on the T cell subgroups, the populations of Th1 and Th2 cells, and the Th1/Th2 cell ratio in these patients.…”
Section: Discussionmentioning
confidence: 96%